Urgensi Transformasi Kurikulum Berbasis Artificial Intelligence Bagi Siswa Di Daerah Kantong Pekerja Migran Indonesia Menuju Zero Skill Mismatch - Fithriatus Shalihah; Haura Salsabiela El Sabrina Nazar; Lubna Aqiela Nazar (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Gaps in the protection of Indonesian migrant workers (PMI) in the pre-placement period. The fact that prospective migrant workers are increasing every year but are not supported by adequate and appropriate skills (Skill-Mismatch). The author has identified 6 factors that cause the ineffective protection of migrant workers that are not prepared to be strengthened during the pre-placement period, including: 1) Problem mindset 2) Discussion and communication obstacles 3) Mentality 4) Lack of understanding of labor law 5) Lack of cultural information about the country of placement and 6) Lack of financial and entrepreneurial literacy. The urgency of strengthening skills for CPMI students as ordered by the PMI Protection Law Number 18 of 2017 is important considering that the implementation of job training by the government through digital services or through government partners is currently not effective. Therefore, curriculum policy innovation is needed for CPMI students so that the above problems can be overcome as early as possible through learning according to skill needs so that CPMI students can receive longer, continuous and programmatic debriefing. This paper examines the gap in the protection of CPMI students during the pre-placement period and contributes thoughts related to the transformation of the AI- based curriculum towards zero skill-mismatch. This research method uses a type of normative law using a legislative approach and theories or expert opinions that are conceptual in nature that are integrated-interconnected. This paper explains that AI- based curriculum transformation requires multistakeholder collaboration. With an adaptive and predictive approach, AI can be a means of supporting skill strengthening for CPMI, in this case CPMI students in PMI enclaves in Indonesia